The benthic community of an intertidal mud flat in the Gulf of Nicoya, Costa Rica. Description of the community - Vargas, José A. (Revista de Biología Tropical, 1987)
Structural changes of the soft-bottom community of a tropical intertidal mud flat (more than 30% silt + clay) in the Gulf of Nicoya, Costa Rica, were evaluated from February, 1984 through February, 1985. Core samples (core area: 17.7 cm2) were collected, at semi-monthly intervals, within a 484 m 2 area and to a depth of 15 cm into the sediment. Samples were preserved in 10% buffered formalin in sea water stained with Rose Bengal. Organisms retained on a 500 mieron mesh sieve were considered as macrofauna. A total of 92 species of macro-invertebrates and the gobiid fish, Gobionellus sagitulla (Gunther) were collected. The community was numerically dominated by deposit feeders. The ostracod, Cyprideis pacifica Hartmann and an undescribed cumacean (Bodotriinae) were the most common organisms found, representing 4 3.4% of the total. The polychaetes, Mediomastus californiensis Hartman, Paraprionospio pinnata (Ehlers), and Lumbrineris tetraura (Schmarda) accounted for 19.2% of the total. An unidentified flatworm (Turbellaria) represented 8.3% of the total number of individuals. Mean density of macro fauna (± 1 SO) was 13,827 ± 10, 1 85 individuals per m2. Diversity (H’) ranged from 1.75 to 3.36 per date (28 cores) and equitability (Evenness) ranged from 0.48 to 0.87. Cluster, principal components, and multiple discriminant analyses revealed a seasonal pattern of the community (dry and rainy seasons). Most species appear to reproduce throughout the year. Peaks of reproductive activity, however, were detected for a group of species. In addition to biological and physical disturbance, spatial and temporal variability of water currents and water characteristics, coupled with an inferred preponderance of planktotrophic larvae, are considered as the main factors promoting changes in community structure. The importance of deposit feeding invertebrates, the types of feeding modes and habitat utilization, and the existence of seasonal patterns, make this community similar to certain temperate zone counterparts. To emphasize these similarities, and for convenience in referring to this assemblage of species, the community is named after a surface deposit-feeding spionid polychaete, a burrowing pinnotherid crab, and a scavenger snail, as the Paraprionospio pinnata - Pinnixa valerii - Nassarius luteostoma community.